Involving supermarkets in health promotion interventions in the Danish Project SoL. A practice-oriented qualitative study on the engagement of supermarket staff and managers - Lise L. Winkler; Ulla Toft; Charlotte Glümer; Paul Bloch; Tine Buch-Andersen; Ulla Christensen (BMC, 2023)
Abstract Background Supermarkets have been suggested as relevant settings for environmental and educational initiatives encouraging healthier shopping and eating decisions, but in the literature, limited attention has been paid to the context, perspectives, and everyday practices of supermarket staff. The aim of this study was to examine the engagement of supermarket staff in a health promotion project from a practice-oriented perspective. Methods The study was based on qualitative data collected in the supermarket setting of Project SoL; a community-based health promotion project in Denmark. We conducted 26 in-depth interviews with store managers and other key staff members in seven participating supermarkets. In addition, we collected data on planning, implementation, and perceptions of supermarket staff of in-store interventions and other project-related activities. These field data included short telephone interviews, observational notes, photos, and audiotapes of meetings. Data were analysed from the perspective of practice theory. Results Although supermarket staff found community-based health promotion meaningful to engage in, the study observed that their engagement was challenged by a business mindset, practical routines and structural requirements favouring sales promotion over health promotion. Nevertheless, there were also examples of how health promotion activities and ways of thinking were successfully incorporated in everyday staff practices during and after Project SoL. Conclusions Our findings point to both potentials and challenges for using supermarkets as settings for health promotion. The voluntary engagement of supermarket staff in community-based health projects cannot stand alone but should be supplemented by more long-lasting strategies and policies regulating this and other food environments. Context-sensitive and practice-oriented analyses in local food environments could inform such strategies and policies to make sure they target unwanted elements and practices and not just individual behavior.